Phytocannabinoids: Useful Drugs for the Treatment of Obesity? Special Focus on Cannabidiol - Bielawiec, Patrycja; Harasim-Symbor, Ewa; Chabowski, Adrian (Frontiers in Endocrinology, 2020)
Currently, an increasing number of diseases related to insulin resistance and obesity is an alarming problem worldwide. It is well known that the above states can lead to the development of type 2 diabetes, hypertension and cardiovascular diseases. An excessive amount of fatty acids (FAs) in a diet also evokes adipocyte hyperplasia and subsequent accumulation of lipids in peripheral organs (liver, cardiac muscle). Therefore, new therapeutic methods are constantly sought for the prevention, treatment and alleviation of symptoms of the above mentioned diseases. Currently, much attention is paid to Cannabis derivatives – phytocannabinoids, which interact with the endocannabinoid system (ECS) constituents. Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) are the most abundant compounds of Cannabis plants and their therapeutic application has been suggested. CBD is considered as a potential therapeutic agent due to its anti-inflammatory, anti-oxidant, anti-tumor, neuroprotective and potential anti-obesity properties. Therefore, in this review, we especially highlight pharmacological properties of CBD as well as its impact on obesity in different tissues.